Kebijakan LAPAS dalam Pembinaan dan Pembentukan Konsep Diri Petugas LPKA pada ANDIKPAS LPKA Kelas II Banda Aceh - Novi Susilawati; Riska Nur Fatikah; Deni Yanuar; Wais Alqarni (Jurnal Pemerintahan dan Politik, 2023)
LPKA is not really a place to punish children with problems, but a place to educate children to become a better generation. This research will look at the policies of prison officers who take place at Class II LPKA Banda Aceh in fostering and forming self-concept towards Andikpas. The research was conducted at LPKA Class II Banda Aceh which is the only institution for fostering children who are in conflict with the law in Aceh Province. The type of approach used is descriptive qualitative. In-depth interviews were conducted with informants who are officers and andikpas at LPKA Class II Banda Aceh. The results of the study show that the coaching process that occurs has a positive impact on where the children are assisted. Andikpas interprets and assesses himself as a child who is in the process of learning. Coaching officers who are significant others have a greater influence on the formation of mind and self in andikpas so as to foster a positive self-concept in andikpas. Andikpas has a change in self-concept from negative to positive self-concept. They can become more organized and focused in life after conducting training at LPKA Class II Banda Aceh. Andikpas' understanding of the coaching process occurs during the coaching process taking place at LPKA. During his time at the coaching institute, andikpas did not feel like he was in a prison where someone who had punished.